Homoclinic orbits and Lie rotated vector fields - Jie Wang; Chen Chen (International Journal of Mathematics and Mathematical Sciences)
Based on the definition of Lie rotated vector fields in the plane, this paper gives the property of homoclinic orbit as parameter is changed and the singular points are fixed on Lie rotated vector fields. It gives the conditions of yielding limit cycles as well.